The Mach stem phenomenon for shaped obstacles buried in soil. (November 2016) - Karinski, Y.S.; Feldgun, V.R.; Racah, E.; Yankelevsky, D.Z.
Abstract: The paper investigates the explosion characteristics of a below ground event of an explosive charge in proximity to a rigid cylindrical obstacle. The two-dimensional study simulates a line explosive and a parallel long cylindrical structure. The investigation shows that the unloading branch has a negligible effect on the peak pressure envelope whereas shear behavior and explosives burning have a considerable effect and should not be disregarded. The effect of the soil's equation of state and especially the full locking parameter on the pressure distribution on an obstacle has been studied. At a short standoff distance where a steep pressure growth beyond the full compaction point is developed, the pressure distributions envelope shows three maxima values that are located at some distance away from the axis of symmetry. It is different than the common single peak along the axis, in the case of a distant explosion. This effect is more pronounced for a medium having sharper pressure growth in the EOS beyond the full compaction point and for smaller charge standoff distances. The pressure distributions analysis indicates that the appearance of second (absolute-primary) and third (secondary) peaks are caused by the Mach stem effect appearing in a soil medium with full locking. The secondary peak pressure envelope maximum corresponds to the secondary Mach stem phenomenon that does not appear in the case of a planar wall, where the incident angle depends on the wave front curvature only.